Acculturation and quality of life in urban, African American caregivers of children with asthma. (20th October 2016) - Everhart, Robin S.; Miadich, Samantha A.; Leibach, Gillian G.; Borschuk, Adrienne P.; Koinis-Mitchell, Daphne
Abstract: Objective : Racial/ethnic minority caregivers of children with asthma are at risk for low levels of quality of life (QOL). Limited research has identified factors that contribute to lower QOL among African American caregivers. This study examined associations between acculturation (e.g., engaging in values/beliefs traditional of one's culture versus adopting mainstream cultural views) and caregiver QOL in low-income, urban African American families of children (7–12 years) with persistent asthma. We also investigated the association between caregiver QOL and child emergency department (ED) use. Methods : Fifty-five caregivers and their children completed interview-based questionnaires in a single research session. Caregivers completed the Pediatric Asthma Caregiver Quality of Life Questionnaire (PACQLQ), the African American Acculturation Scale-Revised (AAAS-R), and reported on child asthma variables. Children completed items assessing asthma control. Results : Higher overall QOL and emotional function subscale scores were associated with more traditional African American religious beliefs/practices ( r = .288, p = .033; r = .333, p = .013). Higher emotional function subscale scores were associated with more traditional values of African American families ( r = .306, p = .023). Lower QOL was found among caregivers of children who had visited the ED three or more times in the last year. Conclusions : Less acculturation tied to religious beliefs/practices and family values (as measured by the AAAS-R) may serve a protective role in reducing the burden low-income, urban African American caregivers experience in managing child asthma. This study is the first of its kind to study acculturation in African American caregivers of children with asthma.